Optimisation of parameters for removal of Methyl Red dye using sawdust as adsorbent - Gunasekar, Therhina (2018)
Utilising agricultural waste, raw sawdust as adsorbent for the removal of Methyl Red (MR) dye as it is a cost effective way. The adsorption process is used because it is found to be more economical and effective compared to other dye removal methods. Fourier Transform Infrared spectroscopy (FTIR) analysis revealed that functional groups such as OH, amine, amide and aromatic ring groups on sawdust proved that it can be used as adsorbent for removal of MR. Various parameters such as particle size, initial dye concentration, adsorbent dosage, contact time, and pH were investigated. The optimum adsorption of Methyl red dye using raw sawdust as biosorbent were found to be at 250 µm of particle size which is worked best on 1000 mg/L initial dye concentration with 1.0 gram of adsorbent in 2 hour time at pH 3 with agitation speed of 150 rpm at 30°C. Adsorption isotherm was studied by using Langmuir and Freundlich isotherm. The best fit line model favoured the Langmuir isotherm with R2 of 0.9947. Langmuir best fit graph indicates that the adsorption that took place is a monolayer adsorption. The highest percentage removal of MR dye was found at 95.14% and it is proven that raw sawdust is potential to remove methyl red dye.